(untitled) (REMUNOM, 2025)
This study aimed to analyze the challenges faced by atypical mothers in the municipality of Colorado do Oeste – RO in accessing public health services provided by SUS. The research used a qualitative approach through semi-structured interviews with mothers of children with disabilities, disorders, or rare conditions. The results show a deep lack of specialized professionals, inadequate infrastructure, lack of psychosocial support, and emotional overload faced by these women. The participants’ statements reveal that, despite existing legal frameworks, public policies have not been sufficient to ensure dignified and humane care. This work highlights the urgent need for more effective, sensitive, and localized public policies that promote comprehensive care for these mothers and their children.